Generative AI vs. Teachers: insights from a literature review [IA generativa versus profesores: reflexiones desde una revisión de la literatura] - Andres Chiappe; Carolina San Miguel; Fabiola Mabel Sáez Delgado (Pixel-Bit)
The growing integration of artificial intelligence in universities is reshaping higher education, particularly through the use of chatbots and generative language models. This article conducts a literature review, applying PRISMA guidelines to 155 peer-reviewed articles, to examine the advantages, limitations, and pedagogical applications of AI compared to human teaching. Three main scenarios of impact on educational practices were identified: a) Loss of certain traditional aspects of teaching, such as exclusive information transmission and reporting tasks, b) Transformation of roles, including control over educational content and the didactic contract, c) Emergence of new elements, such as personalized learning and innovative evaluation approaches. Despite its potential to automate processes and save time, chatbots cannot replicate essential human qualities like empathy and adaptability. Therefore, their optimal integration requires thorough pedagogical analysis to balance innovation with educational effectiveness. This work is valuable for researchers, educators, and instructional designers seeking to understand how to leverage AI without compromising teaching quality. It represents a crucial step toward the development of AI integration strategies grounded in solid pedagogical principles.